2021
DOI: 10.3889/oamjms.2021.6269
|View full text |Cite
|
Sign up to set email alerts
|

Admissions and In-hospital Outcomes of Acute Coronary Syndromes during Corona Virus Disease 19 Pandemic in Albania

Abstract: BACKGROUND: Cardiologists and surveys from all over the world have reported an important drop in admissions of patients with acute coronary syndromes (ACS) and related coronary procedures during the outbreak of coronavirus disease 19 (COVID 19) pandemic. AIM: We investigated the impact of the COVID 19 pandemic on hospitalizations for ACS and related invasive procedures in a country with low COVID 19 incidence. METHODS: We conducted a single-center, observational retrospective study including all consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…In contrast, the proportion of hypertension observed in this systematic review and meta-analysis was lower than in studies done in Slovakia (83.5%) and Albania (90.6%) [ 11 , 14 ]. This variation might be due to lack of diagnostic modalities and proficiency in our setting.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…In contrast, the proportion of hypertension observed in this systematic review and meta-analysis was lower than in studies done in Slovakia (83.5%) and Albania (90.6%) [ 11 , 14 ]. This variation might be due to lack of diagnostic modalities and proficiency in our setting.…”
Section: Discussioncontrasting
confidence: 96%
“…Even though, there is advancement in diagnosis and management of ACS, still it is the most common cause of death around the globe including in Ethiopia [ 9 , 10 ]. A study done at Addis Cardiac Hospital, Ethiopia showed that among 300 cardiac patients, 162 (53.7%) of them had ACS [ 11 ]. Moreover lower-income countries are facing a double burden of disease because of the higher prevalence of both communicable and non-communicable diseases particularly cardiovascular diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first release measures began at the end of April and continued through May, restoring the "normal" life [13]. We previously documented a significant reduction of all-ACS (-41.6%) [14] and STEMI admissions (-28%) [15], and also an increase in mortality for all-ACS with a risk ratio (RR) = 2.2 [(1.20-3.89); p=0.01] and STEMI [RR =1.91 (1.039-3.52) p=0.037] during the lockdown in 2020 compared to the pre-pandemic (PP) period.…”
Section: Introductionmentioning
confidence: 99%